Analisis Yuridis Meningkatnya Pemutusan Hubungan Kerja di Bidang Manufaktur Khususnya Industri Tekstil dan Keadilan Bagi Industri Lokal di Bidang Perdagangan - Sheefa Almaira Koswandi; Christin Septina Basani (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
In recent months, Indonesia has faced a major challenge in global competition and unfavorable import policies towards local products, especially in the textile industry. In this condition, many companies have carried out mass layoffs as an efficient step for which government policies in the field of trade are needed. The approach taken is Normative Juridical, by analyzing laws and regulations related to employment and trade such as Law Number 13 of 2003 concerning Manpower, Law Number 11 of 2020 concerning Job Creation, and Regulation of the Minister of Trade Number 8 of 2024 which is the Third Amendment to Regulation of the Minister of Trade Number 36 of 2023 concerning Import Policy and Regulation, as well as a conceptual approach. The results of the study have shown that layoffs in the textile industry have increased due to the flood of imported goods that can reduce local production. The current guidelines are not strict enough to protect local products. Therefore, stricter regulations are needed to control imports and support domestic industries to provide justice in the industrial sector.